HUMAN ASSISTENCE ROBOT USING MOBILE APPLICATION - M.Bhanu chandu, Dr. Kirupa Ganapathy (International Journal of Advanced Science and Technology, 2020)
Individual mechanized associates help lessening the manual undertakings being put by the individuals in their ordinary tasks. The human voice bearings are given to the human mechanized partner remotely, by using a voice request of customer. The robot can perform different improvements, turns, start/stop exercises and move an article beginning with one spot then onto the following and offering things to the developed people in the home. The voice headings are taken care of, using a propelled cell phone. The individual human right hand robot is made for a littler scope controller based stage and can think about its present zone. The practicality of the voice control passed on over a detachment is evaluated through various assessments. Execution is finished with results of the basic examinations. Potential upgrades are in like manner discussed towards potential applications in home, clinical facilities and adventures and compound labs.